Implementation of PMF and FFT Acquisition Design for B1C Signal Based on ASPeCT. Issue 4 (June 2021) - Liu, Xianyang; Yin, Chengxiang; Yu, Qian; Li, Bochen
Abstract: According to the characteristics of BDS B1C signal, there are many sub peaks in the autocorrelation characteristics, which leads to the ambiguity of B1C signal acquisition. In this paper, the characteristics of B1C signal, acquisition strategy and the ambiguity of different acquisition strategies are analyzed. Based on ASPeCT algorithm, PMF and FFT is implemented in FPGA of navigation receiver. The B1C signal is generated by spiren gss9000 satellite signal simulator, and a test scenario is built for the navigation receiver, which proves the effectiveness of B1C signal acquisition.